Long-Term Effects of Maternal Depression during Postpartum and Early Parenthood Period on Child Socioemotional Development - Anna Suarez; Liubov Shraibman; Vera Yakupova (MDPI AG, 2023)
Most research on the impact of maternal depressive symptoms on child development is conducted during the first year postpartum. Findings on long-term effects of maternal depression are still contradictory and underexplored. The present study investigates the long-term impact of maternal depression during the postpartum and early parenthood periods on child behavioral problems at the mean age of 2.25 years. The Edinburgh postnatal depression scale and Beck depression Inventory were used to assess postpartum and early parenthood depression, respectively. The Child Behavior Checklist was used to examine child's behavioral problems. The regression analysis showed statistically significant associations between child behavioral problems and maternal depression during early parenthood and no significant associations with postpartum depression. Four maternal depressive symptoms' trajectories were identified: consistently low, consistently high, decreased, and increased. The children of mothers with consistently high depressive symptoms at both research stages had the most significant total, internalizing, and externalizing problems. Children of mothers whose depressive symptoms decreased over time had the lowest scores in all three domains of behavioral problems. It is extremely important to implement programs for screening and early intervention for maternal mental health problems that could greatly influence the well-being of women and their children's development.